Integrating NMR and multi-LC-MS-based untargeted metabolomics for comprehensive analysis of blood serum samples - Tereza Kacerova; Elisabete Pires; John Walsby-Tickle; Fay Probert; James S.O. McCullagh (Analytica Chimica Acta, 2025)

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Pyrodiversity interacts with rainfall to increase bird and mammal richness in African savannas - Colin M. Beale; Colin J. Courtney Mustaphi; Thomas A. Morrison; Sally Archibald; T. Michael Anderson; Andrew P. Dobson; Jason E. Donaldson; Gareth P. Hempson; James Probert; Catherine L. Parr (Ecology Letters, 2018)
Fire is a fundamental process in savannas and is widely used for management. Pyrodiversity, variation in local fire characteristics, has been proposed as a driver of biodiversity although empirical evidence is equivocal. Using a new measure of pyrodiversity (Hempson et al .), we undertook the first continent‐wide assessment of how pyrodiversity affects biodiversity in protected areas across African savannas. The influence of pyrodiversity on bird and mammal species richness varied with rainfall: strongest support for a positive effect occurred in wet savannas (> 650 mm/year), where species richness increased by 27% for mammals and 40% for birds in the most pyrodiverse regions. Range‐restricted birds were most increased by pyrodiversity, suggesting the diversity of fire regimes increases the availability of rare niches. Our findings are significant because they explain the conflicting results found in previous studies of savannas. We argue that managing savanna landscapes to increase pyrodiversity is especially important in wet savannas.